2018
DOI: 10.1103/physrevd.98.084014
|View full text |Cite
|
Sign up to set email alerts
|

Joule-Thomson expansion of charged Gauss-Bonnet black holes in AdS space

Abstract: Joule-Thomson expansion process is studied for charged Gauss-Bonnet black holes in AdS space. Firstly, in five-dimensional space-time, the isenthalpic curve in T − P graph is obtained and the cooling-heating region is determined. Secondly, the explicit expression of Joule-Thomson coefficient is obtained from the basic formulas of enthalpy and temperature. Our methods can also be applied to van der Waals system as well as other black hole systems. And the inversion curveT (P ) which separates the cooling region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 73 publications
(36 reference statements)
6
52
1
Order By: Relevance
“…We have observed that for the case of linear axions, when they possess standard kinetic term, the inversion curve possesses only one branch, similar to what was obtained in [32][33][34][35][36][37], behavior that differs from the case of Van der Wall fluids. The net effect of the momentum relaxation mechanism, which is controlled by our coupling β, is that the inversion curve is enlarged for higher values of β.…”
Section: Final Commentssupporting
confidence: 75%
See 4 more Smart Citations
“…We have observed that for the case of linear axions, when they possess standard kinetic term, the inversion curve possesses only one branch, similar to what was obtained in [32][33][34][35][36][37], behavior that differs from the case of Van der Wall fluids. The net effect of the momentum relaxation mechanism, which is controlled by our coupling β, is that the inversion curve is enlarged for higher values of β.…”
Section: Final Commentssupporting
confidence: 75%
“…Furthermore, we study the isenthalpic curves for c 1 = −1 and These observations are novel in the following aspects. Comparing with previous works [32][33][34][35][36][37], where only one branch was obtained, we first obtain two branches for the inversion curve, which is similar to the Van der Waals fluids case. However, the minimal inversion temperature is negative unlike the case of Van der Waals fluids.…”
Section: A Planar Black Holes In Massive Gravitysupporting
confidence: 59%
See 3 more Smart Citations